Soft tissue measurements of Iraqi individuals with Cl I and Cl III skeletal pattern: a comparative cephalometric study (Mustansiria Dental Journal, 2018)
This study was planned to compare some of the soft tissue measurements inindividuals with skeletal Cl I and Cl III, to find out the measurements which may beused as a clinical diagnostic aid to discriminate between both skeletal classes.Seventy three digital true lateral cephalometric radiographs of Iraqi adults weredivided according to the ANB angle into 38 skeletal Cl I and 35 Cl III. The soft tissuemeasurements were analyzed using AutoCAD (2007) software computer program.Descriptive statistics were used to describe the measurements, while independentsamples t-test was used to rule out gender differences and skeletal class differences.Gender differences were found significantly in skeletal Cl I for all linearmeasurements; while in Cl III the significant differences were limited to theanteropoterior measurements only (modified profile thickness at upper lip, modifiedprofile thickness at lower lip, upper lip thickness, and lower lip thickness), with nonsignificant difference for vertical linear measurements (upper and lower Lip heightand Mouth height). All angular measurements showed non-significant genderdifferences. Independent samples t-test revealed that the main differences betweenclasses were found in the labiomental and soft tissue profile angles, which weresignificantly higher in Cl III than Cl I, while the modified profile thickness at upperlip was significantly higher in Cl I than Cl III, for both genders and for the totalsample. Lower lip height, mouth height, and the upper lip height also showedsignificant differences between classes but with less importance.The labiomental angle and modified profile thickness at upper lip can be used asdiagnostic aids to discriminate whether the subject has a Cl I or Cl III skeletalrelation.